Yoga: strategy for the improvement of living together and active participation in social of the educational institution in the early childhood education stage - Moratalla Isasi, Silvia (2019)
This article describes the experience in a school with pupils from four to five years of early childhood education (N=72) with whom I worked in an easy and funny way relaxation breathing exercises specific to yoga. The application in the classroom of these exercises almost every day in a practical and funny way allows children to see how attitudes take much calmer, less tense and more self-control. It also encourages their creative potential and talent. It is advisable for students getting into these exercises from four years onwards, because at that age, children know exactly what to expect and what you want from them. Besides, they have the ability to make and control certain body movements.